"Every interaction you have …should be an opportunity to discuss and offer influenza vaccination". Health service perspectives on influenza vaccination promotion and delivery to Aboriginal families living in New South Wales, Australia. Issue 40 (22nd September 2022) - Bolsewicz, Katarzyna T.; Steffens, Maryke S.; Karpish, Larissa; Bullivant, Bianca; Beard, Frank; Clark, Katrina
Abstract: Introduction: There is little research to understand reasons for suboptimal influenza vaccination uptake among Aboriginal people of different ages in Australia. This study aimed to better understand the communication needs and preferences of Aboriginal families (Phase 2) in New South Wales, Australia, and their health service providers (Phase 1), to inform future interventions to improve influenza immunisation coverage in Aboriginal communities. This paper reports from Phase 1 of the study. Material and methods: Aboriginal and non-Aboriginal researchers designed and conducted the study, with cultural governance provided by Aboriginal health care professionals and other community members working within health departments or community healthcare settings across Australia. In Phase 1 we conducted interviews and focus groups with 18 Aboriginal immunisation providers and mainstream immunisation co-ordinators from three geographic areas in New South Wales. We used group-based thematic analysis with a cultural lens and sought participants' feedback prior to finalising results. Results: We identified four themes, framed as opportunities for improvement: better supporting Aboriginal Medical Services as providers of influenza vaccinations; improving the accessibility and appropriateness of mainstream services for Aboriginal families; improving health providers' knowledge of Aboriginal people' influenza risk and their willingness to recommend vaccination; and engaging communities to design influenza vaccination resources. Conclusions: To achieve optimal influenza vaccination coverage, all health services must take responsibility for providing culturally responsive clinical care to Aboriginal families. We suggest that, where possible, mainstream services incorporate elements of the family-centred and broader model of health used by Aboriginal Medical Services. This includes creating a welcoming environment, appropriately identifying and getting to know Aboriginal patients, taking a preventative approach, and opportunistically offering and strongly encouraging influenza vaccination to the individual and their family.